Climate-smart Cocoa in Central America and the Caribbean - Bunn, Christian; Fernández Kolb, Pablo; Wiegel, Jennifer Rebecca; Guharay, Falguni; Hurtado, Ninoska; Lundy, Mark M.; Castro-Llanos, Fabio Alexander (International Center for Tropical Agriculture, 2019)
This brief summarizes the results of participatory workshops and research on the implementation of CSC in Central America. Many of the practices proposed are already known to and used by Central American farmers seeking to reduce the risks for both the quality and quantity of their production. The interventions summarized in this document can be promoted at different technological, organizational, institutional, and policy levels, as they were developed in a participatory manner with regional experts to leverage the prioritization of known practices. These interventions may be implemented immediately to achieve the expected results in the future. Key Messages: Projections for climate change impacts on cocoa production in Central America and the Caribbean indicate that there will be important changes in the future distribution of suitable zones for this crop; the objectives of Climate-smart Cocoa (CSC) are: increasing productivity, adapting to climate change, and mitigating greenhouse gas emissions, with the purpose of building resilient livelihoods; to boost cocoa production in the region in the short and long term, we recommend the implementation of CSC practices; the CSC practices outlined in this document may be implemented immediately. The list was identified and prioritized with experts from Honduras, Nicaragua, Guatemala, the Dominican Republic, and El Salvador, and many practices are already known to farmers; designing efficient adaptation processes within the framework of CSC represents a multidimensional challenge. This document organizes practices according to the following axes: 1) degree of climate change impact: incremental, systemic, or transformational adaptation; 2) type of extreme climate event, as a result of climate variability: intense rains, strong winds and storms, or drought; and 3) stage of crop development: nursery, establishment, or production; implementing CSC practices at a scale requires appropriate strategies and an enabling environment to support farmers.